The complete mitochondrial genome sequence of Hemiculter leucisculus. (3rd September 2015) - Dong, Fang; Tong, Guang-Xiang; Kuang, You-Yi; Zheng, Xian-Hu; Sun, Xiao-Wen
Abstract: The complete mitochondrial genome of Hemiculter leucisculus was determined to be 16, 617 bp. It contains the structure of 22 transfer RNA genes, 13 protein-coding genes, 2 ribosomal RNA genes, and non-coding control region (D-loop). The critical central conserved sequences (CSB-D, CSB-E, and CSB-F) were also detected. The determination of H. leucisculus mitogenome would play an important role in genetic diversity and population vitality in Cyprinidae.